2014
DOI: 10.1002/adfm.201303670
|View full text |Cite
|
Sign up to set email alerts
|

Modification of the Gallium‐Doped Zinc Oxide Surface with Self‐Assembled Monolayers of Phosphonic Acids: A Joint Theoretical and Experimental Study

Abstract: Gallium‐doped zinc oxide (GZO) surfaces, both bare and modified with chemisorbed phosphonic acid (PA) molecules, are studied using a combination of density functional theory calculations and ultraviolet and X‐ray photoelectron spectroscopy measurements. Excellent agreement between theory and experiment is obtained, which leads to an understanding of: i) the core‐level binding energy shifts of the various oxygen atoms belonging to different surface sites and to the phosphonic acid molecules; ii) the GZO work‐fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
46
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(53 citation statements)
references
References 61 publications
7
46
0
Order By: Relevance
“…It is well established that standard local or semilocal DFT functionals tend to underestimate the energy gaps of both molecular and condensed‐phase systems, which can lead to unreliable results for the energy‐level alignments of molecular frontier orbitals with respect to the semiconductor band edges; this level alignment is a critical component in the evaluation of interfacial charge transfer. However, our earlier work on ZnO‐based systems has shown that the PBE+ U functional can provide a description of energy‐level alignment at organic/ZnO interfaces in good agreement with experimental results . Here, to confirm the trends in charge transfer calculated with the PBE+ U functional, we have also carried out calculations on several selected 6T/ZnO and C 60 /ZnO interfaces using the range‐separated functional HSE06 .…”
Section: Average Adsorption Height (Hads See the Text For Definitionsupporting
confidence: 61%
See 2 more Smart Citations
“…It is well established that standard local or semilocal DFT functionals tend to underestimate the energy gaps of both molecular and condensed‐phase systems, which can lead to unreliable results for the energy‐level alignments of molecular frontier orbitals with respect to the semiconductor band edges; this level alignment is a critical component in the evaluation of interfacial charge transfer. However, our earlier work on ZnO‐based systems has shown that the PBE+ U functional can provide a description of energy‐level alignment at organic/ZnO interfaces in good agreement with experimental results . Here, to confirm the trends in charge transfer calculated with the PBE+ U functional, we have also carried out calculations on several selected 6T/ZnO and C 60 /ZnO interfaces using the range‐separated functional HSE06 .…”
Section: Average Adsorption Height (Hads See the Text For Definitionsupporting
confidence: 61%
“…To compare the electronic properties of ZnO interfaced with donor and acceptor monolayers, we first analyze the work‐function change of ZnO upon the adsorption of each monolayer and the charge transfer or redistribution at each interface. As detailed in our earlier work (see also the Supporting Information for details), the total work‐function change (Δ Φ ) can be ascribed to contributions coming from (i) the molecular dipole along the surface normal direction (Δ V mol. ), (ii) the surface geometry relaxation (Δ V geo.rel.…”
Section: Average Adsorption Height (Hads See the Text For Definitionmentioning
confidence: 97%
See 1 more Smart Citation
“…[25] Nonetheless, the In-based metal oxides are not the ideal semiconductor materials for large-area integrated circuits because of the scarcity of In. [26][27][28] As a result, ZnO is usually adopted as the alternative "In-free" active material for metal-oxide-based electronic devices. [29][30][31] In this regard, the electrospun ZnO NFs have the great potential to satisfy all the stringent requirements for practical applications in large-area, low-cost, and high-performance integrated circuits.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, we employed density‐functional theory (DFT) to calculate the O1s surface core‐level shifts for those ZnO surface structures that have been theoretically predicted to occur under certain conditions. As good agreement of our calculations with experiment can be expected , this choice allows us to additionally provide a benchmark for methods of surface‐structure prediction: if an experimental XPS spectrum is observed that finds no counterpart in the results presented below, then the corresponding structure simply has not been found by theory yet and techniques for doing so should be improved.…”
Section: Introductionmentioning
confidence: 95%